Adaptive interpretation of the results of hydrodynamic research considering a wellbore storage - Viktor Leonidovich Sergeev; Vu Quang Duc (Известия Томского политехнического университета: Инжиниринг георесурсов, 2016)
The relevance of the research is caused by the need to increase information values of the results of unsteady hydrodynamic studies of oil reservoirs. The base of the method proposed is the integrated system of pressure recovery curve in the system «reservoir-well» with the variables, time-dependent parameters. The system allows taking into account additional a priori information and wellbore storage. The main aim of the study is to develop and research analyze models and algorithms of adaptive interpretation, which allows determining the parameters of oil reservoirs in the process of hydrodynamics researches in conditions of a priori uncertainty on the model of wellbore storage. The methods used in the study are the theoretical and practical developments in unsteady hydrodynamic well testing, system analysis, system identification, optimization of functions and linear algebra. The problems were solved on the basis of field data of well exploration in oil deposits by the level recovery curve considering expert estimates of the reservoir filtration parameters (reservoir hydroconductivity, reservoir pressure). The paper introduces the results of comparative analysis of the traditional interpretation method in consideration of the influx of well production with interpretation considering wellbore storage as well as the interpretation of the results obtained while using the computer program Saphir. Results. The authors developed the models and algorithms for adaptive identification and interpretation of hydrodynamics researches in conditions of a priori uncertainty on the model of wellbore storage, which allows determining the parameters of oil reservoirs (reservoir hydroconductivity, piezoconductivity and reservoir pressure), the time required to complete a research and taking into account additional a priori information. It is shown that the adaptive interpretation method allows processing (without loss of accuracy) short level recovery curves, obtained within 5-10 hours of hydrodynamic research, that reduces greatly the downtime.